Exosome-Mediated Metastasis: From Epithelial–Mesenchymal Transition to Escape from Immunosurveillance. (July 2016) - Syn, Nicholas; Wang, Lingzhi; Sethi, Gautam; Thiery, Jean-Paul; Goh, Boon-Cher
Abstract : Exosomes are extracellular signalosomes that facilitate eukaryotic intercellular communication under a wide range of normal physiological contexts. In malignancies, this regulatory circuit is co-opted to promote cancer cell survival and outgrowth. Tumour-derived exosomes (TDEs) carry a pro-EMT (epithelial–mesenchymal transition) programme including transforming growth factor beta (TGFβ), caveolin-1, hypoxia-inducible factor 1 alpha (HIF1α), and β-catenin that enhances the invasive and migratory capabilities of recipient cells, and contributes to stromal remodelling and premetastatic niche formation. The integrin expression patterns on TDEs appear to dictate their preferential uptake by organ-specific cells, implying a crucial role of this pathway in organotropic metastasis. Through the expression of immunomodulatory molecules such as CD39 and CD73, TDEs modify the immune contexture of the tumour microenvironment, which could have implications for immunotherapy. Hence, targeting TDE dysregulation pathways, such as the heparanase/syndecan-1 axis, could represent novel therapeutic strategies in the quest to conquer cancer. Trends: Tumour-derived exosomes (TDEs) contain prodigious amounts of epithelial–mesenchymal transition (EMT) inducers, and transduce EMT characteristics in recipient epithelial cells. Exosomes are being implicated in the aetiology of organotropic metastasis owing to their target-homing ability and capacity to form a premetastatic niche at specific organ sites. Exosomes may be hijacked by tumour viruses and may confer oncogenic potential or induce malignant transformation in recipient cells. TDEs have potent immunomodulatory effects that likely foster tumour escape from immunosurveillance. Pharmacological agents that directly or indirectly modulate tumour exosome biogenesis, secretion, and function have also shown promising antimetastatic activity.